Transformation of Social and Labour Relations in Russia in Digitalization Times - G. L. Podvoysky (Вестник Российского экономического университета имени Г. В. Плеханова)
Digitalization exercises different impact on social and labour relations observed between employee and employer during recruitment process, conducting labour functions and terminating labour activity. On the one hand, digitalization fosters a growth in organization efficiency at the expense of cutting transaction costs and optimization of labour processes. At the same time it can lead to serious risks in the sphere of eroding worker’s social capital by reducing intensity of interaction with colleagues, drop in work team cohesion and violations of work-rest balance. Within the frames of the research the author systematized conclusions of 51 investigations studying the impact of digitalization on social and labour relations. The author discusses aspects of regulatory framework of social and labour relations in conditions of digitalization. And finally, aspects were highlighted that exert complex affect on the development of social and labour relations in conditions of digitalization. As a result a conclusion was drawn that digitalization can cause speeding-up of precarization of labour relations.